A new perspective on Australian snow. (5th December 2014) - Fiddes, Sonya Louise; Pezza, Alexandre Bernardes; Barras, Vaughan
Abstract The Australian Alps have a unique climatological, ecological and hydrological environment and play a key role in water supply for southeastern Australia. Using resort observations we compile a new and robust snow accumulation data set. Both maximum snow depth and total snow accumulation have declined over the last 25 years. A significant decreasing trend was observed for the total number of light snow days, whereas the total number of heavy snow occurrences has remained constant. Maximum temperatures are highly related to all snow variables. It is suggested that global warming is already impacting light snowfall events, while heavy events are less affected.